A wind power main shaft and a manufacturing method for improving fatigue resistance thereof

By employing multi-directional upsetting forging, cryogenic pretreatment, composite quenching and tempering heat treatment, and surface strengthening treatment, a fine and uniform tempered sorbite structure and a gradient residual compressive stress field are formed, which solves the problem of insufficient fatigue resistance of wind turbine main shafts and achieves a significant improvement in fatigue life and enhanced safety and reliability.

CN122012904BActive Publication Date: 2026-08-25GUANGDONG INST OF NEW MATERIALS +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610216374.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-02-14
Publication Date
2026-08-25
Estimated Expiration
2046-02-14

AI Technical Summary

Technical Problem

Existing wind turbine main shafts have insufficient fatigue resistance and cannot meet the requirement of an ultra-long design life of more than 20 years, especially in wind turbine main shafts of megawatt level and above.

Method used

The manufacturing method employs multi-directional upsetting and drawing forging, deep cryogenic pretreatment, composite quenching and tempering heat treatment, surface composite strengthening treatment, and low-temperature aging treatment. It includes steps such as high-temperature austenitization, staged quenching, double tempering, supersonic microparticle shot peening, and laser shock peening to form a fine and uniform tempered sorbite structure and a gradient residual compressive stress field.

Benefits of technology

It significantly improves the overall fatigue life of wind turbine main shafts by 50% to 100%, and greatly enhances damage tolerance and safety reliability, especially under harsh working conditions, with fatigue limits reaching 1.5 to 2 times that of traditional methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a kind of wind power main shaft and the manufacturing method for improving its fatigue resistance, belong to wind power equipment key component manufacturing technical field.The method includes the following steps: multi-direction upsetting and drawing forging is carried out to medium carbon alloy steel ingot, and blank is obtained;The blank is cryogenically pretreated, and then heated to room temperature;Then, composite quenching and tempering heat treatment, surface composite strengthening treatment and low-temperature aging treatment are carried out in sequence.The above-mentioned method is easy to operate, can effectively improve the fatigue life of wind power main shaft, compared with the fatigue life of wind power main shaft manufactured by traditional process can be improved by 50%-100%, and the damage tolerance and safety reliability of wind power main shaft under severe working conditions can also be greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of manufacturing technology for key components of wind power generation equipment, and more specifically, to a wind turbine main shaft and a manufacturing method for improving its fatigue resistance. Background Technology

[0002] The wind turbine main shaft is a core load-bearing component in a wind turbine generator set, connecting the rotor to the gearbox (or directly driving the generator). It withstands enormous alternating bending, torsional, and impact loads over long periods, and its fatigue performance directly determines the service life and operational safety of the unit. Currently, large wind turbine main shafts are generally forged from medium-carbon alloy steels such as 42CrMo4 and 34CrNiMo6. The manufacturing process typically includes forging, rough machining, heat treatment, and finish machining. However, the fatigue resistance of wind turbine main shafts produced by this traditional process is still insufficient, especially for megawatt-class and above wind turbine main shafts, making it difficult to meet the requirement of an ultra-long design life of over 20 years.

[0003] In view of this, the present invention is proposed. Summary of the Invention

[0004] The purpose of this invention is to provide a wind turbine main shaft and a manufacturing method for improving its fatigue resistance, so as to solve or improve the above-mentioned technical problems.

[0005] This invention can be implemented as follows: In a first aspect, the present invention provides a manufacturing method for improving the fatigue resistance of wind turbine main shafts, comprising the following steps: performing multi-directional upsetting and drawing forging on medium carbon alloy steel ingots to obtain forging blanks; subjecting the forging blanks to deep cryogenic pretreatment, followed by heating to room temperature; and then sequentially performing composite quenching and tempering heat treatment, surface composite strengthening treatment, and low-temperature aging treatment.

[0006] In an optional embodiment, the medium carbon alloy steel ingot includes at least one of 42CrMo4 steel ingot and 34CrNiMo6 steel ingot.

[0007] In an optional embodiment, the temperature of multi-directional upsetting and drawing forging is 1200℃~1250℃, the forging ratio is ≥6, and the deformation path is alternating between upsetting and drawing.

[0008] In an optional embodiment, the cryogenic pretreatment is carried out at a liquid nitrogen temperature of -80℃ to -196℃, and the holding time is 1h / 100mm cross-sectional thickness to 2h / 100mm cross-sectional thickness.

[0009] In an optional embodiment, the composite quenching and tempering heat treatment includes sequential high-temperature austenitizing treatment, staged quenching treatment, and two tempering treatments.

[0010] In an optional embodiment, the high-temperature austenitizing treatment is carried out under a protective atmosphere, heated to 860°C~890°C, and held at that temperature for 1.2 min / mm section thickness~1.5 min / mm section thickness. And / or, the graded quenching process includes: first quenching and cooling in hot oil at 80℃~120℃ to 300℃~350℃, and then rapidly transferring to a low-temperature salt bath at 180℃~220℃ for 2h~4h; preferably, the transfer is completed within a time of no more than 30s; And / or, the two tempering processes include: first tempering at 580℃~620℃ for 5h~7h, followed by air cooling and then tempering at 30℃~50℃ lower than the first tempering temperature for 5h~7h, followed by air cooling.

[0011] In an optional embodiment, the surface composite strengthening treatment includes sequential supersonic particle peening and laser shock strengthening.

[0012] In an optional embodiment, the diameter of the shot used in the ultrasonic particle shot peening treatment is 0.3 mm to 0.5 mm, the shot peening speed is 70 m / s to 100 m / s, and the treatment time is 3 min to 5 min. And / or, the conditions for laser shock peening treatment include a pulse energy of 28J~32J and a pulse width of 15ns~25ns, forming a residual compressive stress layer of 0.8mm~1.2mm.

[0013] In an optional embodiment, after the ultrasonic microparticles are sprayed, a plastic deformation layer with a depth of 0.3 mm to 0.5 mm is formed.

[0014] In an optional embodiment, a residual compressive stress layer with a depth of 0.8 mm to 1.2 mm is formed after laser shock strengthening treatment.

[0015] In an optional implementation, the low-temperature aging treatment is carried out at 120°C to 150°C for 48 to 72 hours.

[0016] In an optional implementation, a fine grinding process is performed after the low-temperature aging treatment; In an optional implementation, during the fine grinding process, the amount removed on one side is ≤0.05mm.

[0017] Secondly, the present invention provides a wind turbine main shaft, which is obtained by the manufacturing method of any of the foregoing embodiments.

[0018] In an optional implementation, the fatigue limit of the wind turbine main shaft is ≥1000MPa in a rotational bending fatigue test with R=-1.

[0019] The beneficial effects of this invention include: The manufacturing method provided by this invention, through cryogenic pretreatment and composite tempering heat treatment, can obtain a tempered sorbite structure that is finer, more uniform, and has excellent strength and toughness matching from the surface to the core, which is beneficial to improving the intrinsic fatigue strength of the material. Through supersonic particle shot peening and laser shock peening, a residual compressive stress field with a gradient distribution from high to low can be formed near the surface of the object, which can effectively suppress the initiation and propagation of fatigue cracks. By first performing cryogenic treatment to pre-set micro-compressive stress, then performing staged quenching to reduce macro-stress, and then stabilizing surface compressive stress by low-temperature aging, the above process can reasonably control the stress state and minimize harmful tensile stress.

[0020] The manufacturing method provided by this invention can significantly improve the overall fatigue life of wind turbine main shafts compared to products manufactured by traditional processes, and can especially greatly improve their damage tolerance and safety reliability under harsh working conditions. Detailed Implementation

[0021] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.

[0022] The following is a detailed description of the wind turbine main shaft provided by the present invention and the manufacturing method for improving its fatigue resistance.

[0023] This invention provides a manufacturing method for improving the fatigue resistance of wind turbine main shafts, comprising the following steps: S1: Multi-directional upsetting and drawing forging is performed on medium carbon alloy steel ingots to obtain forging blanks.

[0024] In some alternative embodiments, the medium carbon alloy steel ingot may exemplary include at least one of 42CrMo4 steel ingot and 34CrNiMo6 steel ingot.

[0025] In some alternative embodiments, the temperature of multi-directional upsetting and drawing forging is 1200℃~1250℃, the forging ratio is ≥6, and the deformation path is alternating between upsetting and drawing.

[0026] The temperature for multi-directional upsetting and drawing can be 1200℃, 1210℃, 1220℃, 1230℃, 1240℃ or 1250℃, or other values ​​within the range of 1200℃ to 1250℃.

[0027] If the temperature of multi-directional upsetting forging is below 1200℃, it is not conducive to the plastic deformation of the metal and the welding of internal defects, which can easily lead to cracking, uneven structure and excessive forging force. If the temperature of multi-directional upsetting forging is above 1250℃, it is not conducive to grain refinement and performance control, which can easily cause coarse grains, overheating or even burning, and reduce the mechanical properties of the material.

[0028] The forging ratio in multi-directional upsetting forging can be 6, 7, 8, 9, or 10, or other values ​​within the range of ≥6. In some preferred embodiments, the forging ratio is 8.

[0029] If the forging ratio of multi-directional upsetting forging is less than 6, it is not conducive to fully breaking the original as-cast structure, eliminating internal defects and obtaining uniform and refined equiaxed grains, thus resulting in limited improvement in the mechanical properties of the material.

[0030] By performing the above-mentioned multi-directional upsetting forging, the as-cast structure can be fully broken down to obtain a dense forging billet with a reasonable distribution of streamlines.

[0031] S2: The forging billet is subjected to deep cryogenic pretreatment, and then heated to room temperature.

[0032] In some alternative implementations, cryogenic pretreatment can be carried out at a liquid nitrogen temperature of -80°C to -196°C, with a holding time of 1 h / 100 mm cross-sectional thickness to 2 h / 100 mm cross-sectional thickness.

[0033] The cryogenic pretreatment temperature can be -80℃, -100℃, -120℃, -140℃, -160℃, -180℃, or -196℃, or other values ​​within the range of -80℃ to -196℃. If the cryogenic pretreatment temperature is higher than -80℃ (such as -50℃), it is not conducive to fully realizing the low-temperature phase transformation of the material microstructure, the dispersed precipitation of the second phase, and the effective control of internal stress, thus failing to achieve the goals of refining the microstructure, stabilizing dimensions, and improving material properties.

[0034] The holding time for cryogenic pretreatment can be 1h / 100mm section thickness, 1.5h / 100mm section thickness, or 2h / 100mm section thickness, or other values ​​within the range of 1h / 100mm section thickness to 2h / 100mm section thickness.

[0035] If the holding time of cryogenic pretreatment is less than 2 hours per 100 mm section thickness, it is not conducive to the full progress of microstructure transformation and stress relaxation, resulting in incomplete core processes such as residual austenite transformation and carbide dispersion precipitation, which affects the consistency of treatment effect. If the holding time of cryogenic pretreatment is longer than 1 hour per 100 mm section thickness, it is not conducive to improving production efficiency and economic benefits, and may bring diminishing returns or even negative risks due to excessive energy consumption and potential micro-stress redistribution.

[0036] After cryogenic pretreatment, it can slowly rise to room temperature in the air.

[0037] The above-mentioned cryogenic pretreatment and heating process can promote the transformation of residual austenite, refine the microstructure, and pre-set beneficial micro-compressive stress.

[0038] S3: Perform composite tempering heat treatment, surface composite strengthening treatment, and low-temperature aging treatment in sequence.

[0039] In some alternative implementations, the composite quenching and tempering heat treatment includes sequential high-temperature austenitization, staged quenching, and two tempering processes.

[0040] Among them, the high-temperature austenitizing treatment is carried out under a protective atmosphere, heated to 860℃~890℃, and held for 1.2min / mm section thickness~1.5min / mm section thickness.

[0041] The temperature for the above-mentioned high-temperature austenitizing treatment can be 860℃, 870℃, 880℃ or 890℃, or other values ​​within the range of 860℃ to 890℃.

[0042] The holding time for high-temperature austenitizing treatment can be 1.2 min / mm section thickness, 1.3 min / mm section thickness, 1.4 min / mm section thickness, or 1.5 min / mm section thickness, or other values ​​within the range of 1.2 min / mm section thickness to 1.5 min / mm section thickness. If the holding time for high-temperature austenitizing treatment is shorter than 1.5 min / mm section thickness, it is not conducive to the homogenization of austenite composition, the complete dissolution of the original microstructure, and the reaching of the core temperature, resulting in uneven microstructure and substandard performance. If the holding time for high-temperature austenitizing treatment is longer than 1.2 min / mm section thickness, it is not conducive to grain size control and production cost control, easily leading to coarse grains, surface decarburization or overheating, and reduced production efficiency.

[0043] The above-mentioned high-temperature austenitization treatment ensures that the alloying elements are fully dissolved.

[0044] The graded quenching process includes: first quenching and cooling in hot oil at 80℃~120℃ to 300℃~350℃, and then quickly transferring it to a low-temperature salt bath at 180℃~220℃ for 2h~4h.

[0045] The temperature of the hot oil can be 80℃, 90℃, 100℃, 110℃ or 120℃, or other values ​​within the range of 80℃ to 120℃.

[0046] The final temperature for quenching and cooling in hot oil can be 300℃, 310℃, 320℃, 330℃, 340℃ or 350℃, or other values ​​within the range of 300℃ to 350℃.

[0047] If the final temperature of quenching and cooling in hot oil is below 300℃, it is not conducive to controlling the process of martensitic transformation and structural stress, which may increase the deformation and cracking tendency of the workpiece and reduce production efficiency. If the final temperature of quenching and cooling in hot oil is above 350℃, it is not conducive to inhibiting the formation of non-martensitic structures, which may lead to insufficient hardness, insufficient quenching depth and uneven performance of the workpiece.

[0048] Ideally, the transfer should be completed within 30 seconds. If the transfer speed is too slow, the workpiece may undergo a high-temperature non-martensitic transformation during the transfer process, resulting in insufficient quenching hardness, uneven structure, and may cause excessive thermal stress and structural stress, increasing the risk of deformation and cracking.

[0049] The temperature of the low-temperature salt bath can be 180℃, 190℃, 200℃, 210℃ or 220℃, or other values ​​within the range of 180℃ to 220℃.

[0050] If the temperature of the low-temperature salt bath is below 180℃, it is not conducive to the effective diffusion and homogenization of alloying elements, which may lead to insufficient microstructure transformation or residual stress. If the temperature of the low-temperature salt bath is above 220℃, it may cause over-tempering, excessive grain growth, or a decrease in hardness / strength beyond the allowable range of the process, thus damaging the final performance.

[0051] The holding time for the low-temperature salt bath can be 2h, 2.5h, 3h, 3.5h or 4h, or other values ​​within the range of 2h to 4h.

[0052] The above-described graded quenching process can complete the martensitic transformation and significantly reduce structural stress and quenching deformation. Specifically, quenching in hot oil can reduce workpiece deformation and cracking tendency; low-temperature salt bath quenching can stabilize the microstructure, eliminate stress, and adjust the final properties.

[0053] In some optional embodiments, the two tempering processes include: first tempering at 580°C to 620°C for 5 to 7 hours, followed by air cooling and then tempering at 30°C to 50°C lower than the first tempering temperature for 5 to 7 hours, and then air cooling.

[0054] The initial tempering temperature can be 580℃, 590℃, 600℃, 610℃ or 620℃, or other values ​​within the range of 580℃ to 620℃.

[0055] The initial tempering time can be 5h, 5.5h, 6h, 6.5h or 7h, or other values ​​within the range of 5h to 7h.

[0056] The temperature of the second tempering can be 30°C, 35°C, 40°C, 45°C or 50°C lower than the temperature of the first tempering, or any other value within the range of 30°C to 50°C lower than the temperature of the first tempering.

[0057] Controlling the temperature of the second tempering to be 30°C to 50°C lower than that of the first tempering can prevent temper brittleness and further reduce residual stress.

[0058] The holding time for secondary tempering can be 5h, 5.5h, 6h, 6.5h or 7h, or other values ​​within the range of 5h to 7h.

[0059] The above two tempering processes can further stabilize the microstructure and precipitate uniform and fine carbides.

[0060] In some alternative embodiments, the surface composite strengthening treatment includes sequential supersonic particle peening and laser shock peening.

[0061] It should be noted that in this invention, the surface composite strengthening treatment is applied to all outer surfaces of the wind turbine main shaft (including stress concentration areas such as variable diameter fillets and keyways).

[0062] The ultrasonic particle shot peening treatment uses shot with a diameter of 0.3mm to 0.5mm, a shot peening speed of 70m / s to 100m / s, and a treatment time of 3min to 5min.

[0063] The diameter of the shot peening can be 0.3mm, 0.35mm, 0.4mm, 0.45mm or 0.5mm, or other values ​​within the range of 0.3mm to 0.5mm.

[0064] The shot peening velocity can be 70m / s, 80m / s, 90m / s or 100m / s, or other values ​​within the range of 70m / s to 100m / s.

[0065] The shot peening treatment time can be 3 min, 4 min, or 5 min, or other values ​​within the range of 3 min to 5 min.

[0066] The above-mentioned ultrasonic microparticle spraying treatment can form a plastic deformation layer with a depth of 0.3mm to 0.5mm on the surface of the object.

[0067] Laser shock peening treatment involves using laser shock peening equipment to process along the spindle axis and fillet. The conditions for laser shock peening treatment may include: pulse energy of 28J~32J (such as 28J, 30J or 32J, etc.) and pulse width of 15ns~25ns (such as 15ns, 20ns or 25ns, etc.).

[0068] Through the above-mentioned laser shock strengthening treatment, a residual compressive stress layer with a depth of 0.8mm to 1.2mm can be formed on the surface of the object.

[0069] In some alternative implementations, the low-temperature aging treatment is carried out at 120°C to 150°C for 48 to 72 hours.

[0070] The temperature for low-temperature aging treatment can be 120℃, 130℃, 140℃ or 150℃, or other values ​​within the range of 120℃ to 150℃.

[0071] The temperature for low-temperature aging treatment can be 48h, 54h, 60h, 66h or 72h, or other values ​​within the range of 48h to 72h.

[0072] Low-temperature aging treatment can stabilize the residual compressive stress generated by surface composite strengthening treatment and promote the relaxation and homogenization of micro-stress.

[0073] S4: Fine grinding process.

[0074] In some alternative implementations, during the fine grinding process, the amount removed on one side is ≤0.05mm to retain the majority of the reinforcing layer.

[0075] Furthermore, it can also perform 100% ultrasonic testing and surface magnetic particle testing.

[0076] Building upon the above, the manufacturing method provided by this invention, through cryogenic pretreatment and composite tempering heat treatment, can obtain a tempered sorbite structure that is finer, more uniform, and exhibits excellent strength and toughness matching from the surface to the core, thereby increasing the intrinsic fatigue strength of the material by more than 15%. Through supersonic particle shot peening and laser shock peening, a gradient-distributed residual compressive stress field (peak compressive stress reaching over -800 MPa) with a depth of over 1 mm can be formed near the surface of the object, effectively suppressing the initiation and propagation of fatigue cracks. By first performing cryogenic treatment to pre-set micro-compressive stress, then staged quenching to reduce macro-stress, and finally low-temperature aging to stabilize surface compressive stress, the stress state can be rationally controlled, minimizing harmful tensile stress. Therefore, the manufacturing method provided by this invention can increase the overall fatigue life of wind turbine main shafts by 50%-100% compared to products manufactured using traditional processes, especially significantly improving damage tolerance and safety reliability under harsh operating conditions.

[0077] Accordingly, the present invention also provides a wind turbine main shaft, which is obtained by the above-described manufacturing method.

[0078] In some alternative implementations, the fatigue limit of the wind turbine main shaft is ≥1000MPa in a rotational bending fatigue test with R=-1.

[0079] The features and performance of the present invention will be further described in detail below with reference to embodiments.

[0080] Example 1 This embodiment provides a 5MW wind turbine main shaft, the preparation method of which includes: S1: Multi-directional upsetting and drawing forging of medium carbon alloy steel ingots to obtain forging blanks with a diameter of 500mm.

[0081] Among them, the medium carbon alloy steel ingot is 42CrMo4 steel ingot.

[0082] The temperature for multi-directional upsetting and drawing forging is 1220℃, the forging ratio is 6, and the deformation path is alternating between upsetting and drawing.

[0083] S2: The forging billet is subjected to deep cryogenic pretreatment and then slowly restored to room temperature in air.

[0084] The cryogenic pretreatment was carried out at a liquid nitrogen temperature of -196℃, and the holding time was 1.5h / 100mm cross-sectional thickness (that is, the holding time of the cryogenic pretreatment was 3h).

[0085] S3: Perform composite tempering heat treatment, surface composite strengthening treatment, and low-temperature aging treatment in sequence.

[0086] S3-1: The composite quenching and tempering heat treatment includes high-temperature austenitization, graded quenching, and two tempering processes performed sequentially.

[0087] The high-temperature austenitizing treatment is carried out under a protective atmosphere, heated to 870℃, and held for 1.5 min / mm cross-sectional thickness (that is, the holding time of the high-temperature austenitizing treatment is 5 h).

[0088] The graded quenching process includes: first quenching in hot oil at 100°C and cooling to 320°C, then rapidly transferring to a low-temperature salt bath at 200°C within 30 seconds and holding for 3 hours.

[0089] The two tempering processes consist of: first tempering at 600℃ for 6 hours, followed by air cooling and then tempering at 40℃ lower temperature than the first tempering temperature (i.e., the second tempering temperature is 560℃) for 6 hours, and then air cooling.

[0090] S3-2: Supersonic particle shot peening and laser shock peening are performed sequentially on all outer surfaces of the wind turbine main shaft (including stress concentration areas such as diameter-changing fillets and keyways).

[0091] Among them, ultrasonic particle peening involves using cast steel shot with a diameter of 0.4 mm at a speed of 85 m / s for full coverage peening, with a treatment time of 5 minutes. After ultrasonic particle peening, a plastic deformation layer with a depth of 0.4 mm is formed on the surface of the object.

[0092] Laser shock peening is a process that uses laser shock peening equipment to treat the workpiece along the spindle axis and fillet radius. The conditions for laser shock peening include a pulse energy of 30 J and a pulse width of 20 ns. After laser shock peening, a residual compressive stress layer with a depth of 1 mm is formed on the surface of the workpiece.

[0093] S3-3: Low-temperature aging treatment is carried out at 135℃ for 60 hours.

[0094] S4: Perform fine grinding.

[0095] During the fine grinding process, the amount removed on one side is <0.05mm.

[0096] S5: Perform 100% ultrasonic testing and surface magnetic particle testing.

[0097] Example 2 This embodiment provides a 5MW wind turbine main shaft, the preparation method of which includes: S1: Multi-directional upsetting and drawing forging of medium carbon alloy steel ingots to obtain forging blanks with a diameter of 400mm.

[0098] Among them, the medium carbon alloy steel ingot is 42CrMo4 steel ingot.

[0099] The temperature for multi-directional upsetting and drawing forging is 1200℃, the forging ratio is 8, and the deformation path is alternating between upsetting and drawing.

[0100] S2: The forging billet is subjected to deep cryogenic pretreatment and then slowly restored to room temperature in air.

[0101] The cryogenic pretreatment was carried out at a liquid nitrogen temperature of -80℃, and the holding time was 2h / 100mm cross-sectional thickness (that is, the holding time of the cryogenic pretreatment was 5h).

[0102] S3: Perform composite tempering heat treatment, surface composite strengthening treatment, and low-temperature aging treatment in sequence.

[0103] S3-1: The composite quenching and tempering heat treatment includes high-temperature austenitization, graded quenching, and two tempering processes performed sequentially.

[0104] Among them, the high-temperature austenitizing treatment is carried out under a protective atmosphere, heated to 860℃, and held for 1.5 min / mm cross-sectional thickness.

[0105] The graded quenching process includes: first quenching in hot oil at 80°C and cooling to 350°C, then rapidly transferring to a low-temperature salt bath at 180°C within 30 seconds and holding for 4 hours.

[0106] The two tempering processes consist of: first tempering at 580℃ for 7 hours, followed by air cooling and then tempering at 550℃ (30℃ lower than the first tempering temperature) for 7 hours, and finally air cooling.

[0107] S3-2: Supersonic particle shot peening and laser shock peening are performed sequentially on all outer surfaces of the wind turbine main shaft (including stress concentration areas such as diameter-changing fillets and keyways).

[0108] Among them, ultrasonic particle peening involves using cast steel shot with a diameter of 0.3 mm at a speed of 100 m / s for full coverage peening, with a treatment time of 3 minutes. After ultrasonic particle peening, a plastic deformation layer with a depth of 0.3 mm is formed on the surface of the object.

[0109] Laser shock peening is a process that uses laser shock peening equipment to treat the workpiece along the spindle axis and fillet radius. The conditions for laser shock peening include a pulse energy of 30 J and a pulse width of 20 ns. After laser shock peening, a residual compressive stress layer with a depth of 0.8 mm is formed on the surface of the workpiece.

[0110] S3-3: Low-temperature aging treatment was carried out at 120℃ for 72 hours.

[0111] S4: Perform fine grinding.

[0112] During the fine grinding process, the amount removed on one side is <0.05mm.

[0113] S5: Perform 100% ultrasonic testing and surface magnetic particle testing.

[0114] Example 3 This embodiment provides a 5MW wind turbine main shaft, the preparation method of which includes: S1: Multi-directional upsetting and drawing forging of medium carbon alloy steel ingots to obtain forging blanks with a diameter of 300mm.

[0115] Among them, the medium carbon alloy steel ingot is 42CrMo4 steel ingot.

[0116] The temperature for multi-directional upsetting and drawing forging is 1250℃, the forging ratio is 7, and the deformation path alternates between upsetting and drawing.

[0117] S2: The forging billet is subjected to deep cryogenic pretreatment and then slowly restored to room temperature in air.

[0118] The cryogenic pretreatment was carried out at a liquid nitrogen temperature of -150℃, and the holding time was 1h / 100mm cross-sectional thickness (that is, the holding time of the cryogenic pretreatment was 3h).

[0119] S3: Perform composite tempering heat treatment, surface composite strengthening treatment, and low-temperature aging treatment in sequence.

[0120] S3-1: The composite quenching and tempering heat treatment includes high-temperature austenitization, graded quenching, and two tempering processes performed sequentially.

[0121] The high-temperature austenitizing treatment is carried out under a protective atmosphere, heated to 890℃, and held for 1.2 min / mm cross-sectional thickness (that is, the holding time for the high-temperature austenitizing treatment is 250 min).

[0122] The graded quenching process includes: first quenching in hot oil at 120°C and cooling to 300°C, then rapidly transferring to a low-temperature salt bath at 220°C within 30 seconds and holding for 2 hours.

[0123] The two tempering processes consist of: first, holding at 620℃ for 5 hours for the first tempering, then air cooling, followed by holding at 50℃ lower than the first tempering temperature (i.e., the second tempering temperature is 570℃) for 5 hours for the second tempering, and then air cooling.

[0124] S3-2: Supersonic particle shot peening and laser shock peening are performed sequentially on all outer surfaces of the wind turbine main shaft (including stress concentration areas such as diameter-changing fillets and keyways).

[0125] Among them, ultrasonic particle peening involves using cast steel shot with a diameter of 0.5 mm at a speed of 70 m / s for full coverage peening, with a treatment time of 5 minutes. After ultrasonic particle peening, a plastic deformation layer with a depth of 0.5 mm is formed on the surface of the object.

[0126] Laser shock peening is a process that uses laser shock peening equipment to treat the workpiece along the spindle axis and fillet radius. The conditions for laser shock peening include a pulse energy of 30 J and a pulse width of 20 ns. After laser shock peening, a residual compressive stress layer with a depth of 1.2 mm is formed on the surface of the workpiece.

[0127] S3-3: Low-temperature aging treatment is carried out at 150℃ for 48 hours.

[0128] S4: Perform fine grinding.

[0129] During the fine grinding process, the amount removed on one side is <0.05mm.

[0130] S5: Perform 100% ultrasonic testing and surface magnetic particle testing.

[0131] Example 4 The difference between this embodiment and Embodiment 1 is that in S1, the medium carbon alloy steel ingot is a 34CrNiMo6 steel ingot.

[0132] Comparative Example 1 The difference between this comparative example and Example 1 is that in S1, the temperature of the multi-directional upsetting forging is 1100°C.

[0133] Comparative Example 2 The difference between this comparative example and Example 1 is that in S1, the temperature of the multi-directional upsetting forging is 1300°C.

[0134] Comparative Example 3 The difference between this comparative example and Example 1 is that in S1, the forging ratio of multi-directional upsetting forging is 5.

[0135] Comparative Example 4 The difference between this comparative example and Example 1 is that the cryogenic pretreatment of S2 was not performed.

[0136] Comparative Example 5 The difference between this comparative example and Example 1 is that in S3, the sample was not quenched and cooled in hot oil, but directly subjected to a low-temperature salt bath.

[0137] Comparative Example 6 The difference between this comparative example and Example 1 is that in S3, only quenching and cooling in hot oil were performed, without a low-temperature salt bath.

[0138] Comparative Example 7 The difference between this comparative example and Example 1 is that in S3, only the first tempering is performed.

[0139] Comparative Example 8 The difference between this comparative example and Example 1 is that in S3, supersonic particle peening was not performed.

[0140] Comparative Example 9 The difference between this comparative example and Example 1 is that in S3, no laser shock strengthening treatment was performed.

[0141] Test case The wind turbine main shafts prepared in Examples 1-4 and Comparative Examples 1-9 were subjected to rotational bending fatigue tests with R=-1, and the test methods were based on GB / T 4337-2015 "Fatigue Test of Metallic Materials - Rotational Bending Method". The results are shown in Table 1.

[0142] Table 1 Performance Results

[0143] As can be seen from Table 1, compared with Comparative Examples 1-9, the wind turbine main shafts prepared in Examples 1-4 of the present invention have significantly better fatigue resistance.

[0144] Furthermore, by comparing the fatigue resistance performance with that of existing wind turbine main shafts under the same conditions, the fatigue limit (10) of the wind turbine main shaft provided by this invention is higher. 7 The number of cycles can reach 1.5 to 2 times that of traditional wind turbine main shafts, and the plastic deformation layer and residual compressive stress layer formed by the surface composite strengthening treatment are stable.

[0145] In summary, the manufacturing method provided by this invention, through cryogenic pretreatment and composite tempering heat treatment, can obtain a finer, more uniform, and better-matched tempered sorbite structure from the surface to the core, improving the intrinsic fatigue strength of the material by more than 15%. Through supersonic particle shot peening and laser shock peening, a gradient-distributed residual compressive stress field (peak compressive stress reaching over -800 MPa) with a depth of over 1 mm can be formed near the surface of the object, effectively suppressing the initiation and propagation of fatigue cracks. By first performing cryogenic treatment to pre-set micro-compressive stress, then staged quenching to reduce macro-stress, and finally low-temperature aging to stabilize surface compressive stress, the stress state can be reasonably controlled, minimizing harmful tensile stress. Therefore, the manufacturing method provided by this invention can increase the overall fatigue life of wind turbine main shafts by 50% to 100% compared to products manufactured using traditional processes, especially significantly improving damage tolerance and safety reliability under harsh operating conditions.

[0146] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A manufacturing method for improving the fatigue resistance of wind turbine main shafts, characterized in that, Includes the following steps: Medium carbon alloy steel ingots are subjected to multi-directional upsetting and drawing forging to obtain forging blanks; The forging billet is subjected to deep cryogenic pretreatment, and then heated to room temperature; Then, composite tempering heat treatment, surface composite strengthening treatment, and low-temperature aging treatment are carried out in sequence. The medium carbon alloy steel ingot includes at least one of 42CrMo4 steel ingot and 34CrNiMo6 steel ingot; The temperature for multi-directional upsetting forging is 1200℃~1250℃, and the forging ratio is ≥6; The composite quenching and tempering heat treatment includes sequential high-temperature austenitization, staged quenching, and two tempering processes. The surface composite strengthening treatment includes sequential supersonic particle shot peening and laser shock strengthening treatment.

2. The manufacturing method according to claim 1, characterized in that, The deformation path of multi-directional upsetting and drawing forging is an alternation of upsetting and drawing.

3. The manufacturing method according to claim 1, characterized in that, The cryogenic pretreatment was carried out at a liquid nitrogen temperature of -80℃ to -196℃, with a holding time of 1h / 100mm cross-sectional thickness to 2h / 100mm cross-sectional thickness.

4. The manufacturing method according to claim 1, characterized in that, High-temperature austenitizing treatment is carried out under a protective atmosphere, heated to 860℃~890℃, and held for 1.2 min / mm section thickness~1.5 min / mm section thickness; And / or, graded quenching treatment includes: first quenching in hot oil at 80℃~120℃ and cooling to 300℃~350℃, then quickly transferring to a low-temperature salt bath at 180℃~220℃ and holding for 2h~4h; And / or, the two tempering processes include: first tempering at 580℃~620℃ for 5h~7h, followed by air cooling and then tempering at 30℃~50℃ lower than the first tempering temperature for 5h~7h, followed by air cooling.

5. The manufacturing method according to claim 1, characterized in that, The shot diameter used in ultrasonic particle peening is 0.3mm~0.5mm, the shot velocity is 70m / s~100m / s, and the treatment time is 3min~5min. And / or, the conditions for laser shock peening treatment include: pulse energy of 28J~32J, pulse width of 15ns~25ns, forming a residual compressive stress layer of 0.8mm~1.2mm.

6. The manufacturing method according to claim 5, characterized in that, After ultrasonic microparticle spraying, a plastic deformation layer with a depth of 0.3mm to 0.5mm is formed.

7. The manufacturing method according to claim 5, characterized in that, Laser shock peening treatment forms a residual compressive stress layer with a depth of 0.8mm to 1.2mm.

8. The manufacturing method according to claim 1, characterized in that, Low-temperature aging treatment was carried out at 120℃~150℃ for 48h~72h.

9. The manufacturing method according to claim 1, characterized in that, After low-temperature aging treatment, it undergoes fine grinding.

10. The manufacturing method according to claim 9, characterized in that, During the fine grinding process, the amount removed on one side is ≤0.05mm.

11. A wind turbine main shaft, characterized in that, Obtained by the manufacturing method according to any one of claims 1 to 10.

12. The wind turbine main shaft according to claim 11, characterized in that, In the rotational bending fatigue test with R=-1, the fatigue limit of the wind turbine main shaft is ≥1000MPa.

Citation Information

Patent Citations

  • Wind power bearing for wind driven generator

    CN105220076A

  • 12.9-grade wind power bolt material as well as preparation method and application thereof

    CN120666249A